Indian Cinema and Cultural Identity: Negotiating Tradition, Modernity, and Global Influence - Santanu Sarkar; Anuradha Choudry (IAFOR Journal of Cultural Studies)
Indian cinema, particularly Bollywood, has played a pivotal role in shaping cultural identity by blending traditional storytelling with contemporary cinematic techniques. Recent scholarship on Indian cinema has increasingly focused on Indian identity, cultural hybridity, transnational cinema, and Bollywood’s role as a vehicle of soft power in global media. Following this, the present study explores how Indian cinema negotiates the intersection of tradition, modernity, and globalization through a multidisciplinary approach that integrates classical Indian aesthetics—particularly Rasa Theory’s emotional framework, alongside Western cinematic traditions, postcolonial discourse, and transnational cinema as a global context. Seven films— Pather Panchali (Ray, 1955), Mughal-e-Azam (Asif, 1960), Lagaan (Gowariker, 2001), The Lunchbox (Batra, 2013), Rustom (Desai, 2016), Gully Boy (Akhtar, 2019) and All We Imagine as Light (Kapadia, 2024)—are analyzed to examine how Indian filmmakers sustain aesthetic continuity while adapting to evolving global conventions. Findings reveal that Indian cinema blends indigenous aesthetics with contemporary cinematic forms, resulting in culturally hybrid and emotionally resonant narratives. Rasa aesthetics shape the emotional and visual texture across all seven films, while localized Western conventions address themes of resistance, aspiration, and social justice, alongside postcolonial concerns such as nationalism, caste, and gender. Moreover, its growing global reach reflects a shift toward transnational storytelling rooted in cultural specificity. This study contributes to broader discussions on cultural hybridity, national identity, and global cinema, underscoring Indian cinema’s dual role as both a preserver of tradition and a dynamic, evolving force in the international media landscape.